The ‘shifting’ nature of theory in international relations: why the future of the discipline is its Waltzian past - Coetzee, Eben; Solomon, Hussein (University of the Free State, 2014)
Within the discipline of International Relations (IR), ‘new’ conceptions of theory, specifically those subscribing to, on the one hand, an inductivist and empiricist conception of theory, and, on the other hand, a conception of theory as a loose collection of variables, have ostensibly challenged the conception of theory as advanced by Kenneth Waltz. The latter’s conception of theory, deeply embedded within the philosophy-of-science literature, illustrates that the essential qualities of theories are wholly irreconcilable with the conception(s) of theory as advanced by current scholars within the discipline. Moreover, despite the commonplace assumption that scholars have transcended Waltz’s work, scholars continue, however, to err by misinterpreting him on the nature of theory and by failing to heed the explanatory benefits emanating from his conception of theory. Contra the current vogue in IR, then, we argue that the anti-Waltzian conception(s) of theory is neither particularly new nor does it bode well for the explanatory ideals of the discipline.
Keywords: International relations; Waltz, Kenneth